Impact of fatigue on positional movements during professional rugby union match play - Tee, J. C.; Lambert, M. I.; Coopoo, Y. (International Journal of Sports Physiology and Performance, 2017)
Purpose: In team sports, fatigue is manifested by a self-regulated decrease in movement distance and intensity. There is currently limited information on the effect of fatigue on movement patterns in rugby union match play, particularly for players in different position groups (backs vs forwards). This study investigated the effect of different match periods on movement patterns of professional rugby union players.